A Review of Sulfate Removal from Water Using Polymeric Membranes - Jamal Al Mehrate; Sadek Shaban; Amr Henni (Membranes)
Access to clean and reliable water has become a critical concern due to the global water crisis. High sulfate levels in drinking water raise health concerns for humans and animals and can cause serious corrosion in industrial systems. Sulfated waters represent a major challenge on the Canadian prairies, leading to many cattle deaths. While reverse osmosis (RO) membranes effectively remove sulfates, they are costly due to high-pressure requirements. Nanofiltration (NF) membranes present a more affordable alternative, outperforming traditional methods like adsorption, desalination, and ion exchange. Developing low-pressure ultrafiltration (UF) and microfiltration (MF) membranes could also reduce costs. This review explores advancements in polymeric materials and membrane technology to enhance sulfate removal, focusing on methods used to reduce fouling and improve permeate flux. Techniques discussed include phase inversion (PI), thin-film composite (TFC), and thin-film nanocomposite (TFN) membranes. The review also highlights recent fabrication methods for pristine and nanomaterial-enhanced membranes, acknowledging both benefits and limitations. Continued innovations in polymer-based membranes are expected to drive further performance and cost-efficiency improvements. This review found that studies in the literature dealt mainly with sulfate concentrations below 2000 mg/L, indicating a need to address higher concentrations in future studies.